1993
DOI: 10.1083/jcb.120.3.785
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil migration across cultured intestinal epithelial monolayers is modulated by epithelial exposure to IFN-gamma in a highly polarized fashion.

Abstract: Abstract. Neutrophil, or polymorphonuclear leukocyte (PMN), migration across intestinal epithelial barriers, such as occurs in many disease states, appears to result in modifications of epithelial barrier and ion transport functions (Nash, S., J. Stafford, and J. L. . Z Clin. Invest. 80:1104-1113; Madara, J. L., C. A. Parkos, S. P. Colgan, R. J. MacLeod, S. Nash, J. B. Matthews, C. Delp, and W. I. Lencer. 1992. J. Clin. Invest. 89:1938-1944). Here we investigate the effects of epithelial exposure to IFN-,), o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
111
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(125 citation statements)
references
References 40 publications
(89 reference statements)
13
111
1
Order By: Relevance
“…Thus, IFN-␥ may enhance the expression of ICAM-1, thereby inducing neutrophil transmigration. Furthermore, IFN-␥ can augment neutrophil transmigration through a monolayer of the human intestinal cell line, T84, in vitro (46). Taken collectively, locally produced IFN-␥ may enhance neutrophil transmigration directly and/or indirectly by enhancing chemokine production and ICAM-1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, IFN-␥ may enhance the expression of ICAM-1, thereby inducing neutrophil transmigration. Furthermore, IFN-␥ can augment neutrophil transmigration through a monolayer of the human intestinal cell line, T84, in vitro (46). Taken collectively, locally produced IFN-␥ may enhance neutrophil transmigration directly and/or indirectly by enhancing chemokine production and ICAM-1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…16,17,26 Nonetheless, recent studies have suggested that integrin-mediated adhesion may potentate PMN degranulation. 27 Because our transmigration assay uses MPO as a biochemical marker, we ruled out that these findings with wortmannin could result from differences in MPO content.…”
Section: Pi3k Inhibitors Promote Transmigrationmentioning
confidence: 99%
“…To assay RAGE expression in T84 cells after inflammatory cytokine treatment, we incubated T84 monolayers with a culture medium containing TNF-␣ (20 ng/ml) or IFN-␥ (10 ng/ml), or a combination of the two, for 24, 48, and 72 h, respectively (34,35). After washing, the monolayers were fixed, blocked with 5% normal goat serum or BSA, followed by incubation with anti-RAGE Abs and labeling with Alexa Fluor-conjugated secondary Abs.…”
Section: Cytokine Treatment and Rage Measurementmentioning
confidence: 99%
“…To test whether RAGE plays a role in intestinal inflammation, we examined RAGE expression in intestinal epithelial monolayers treated with or without proinflammatory cytokines. In these experiments, T84 monolayers were cultured in the presence or absence of TNF-␣ and/or IFN-␥ for various time intervals (34,35), and the expression of RAGE in T84 cells was analyzed by immunofluorescence staining. We observed that RAGE expression along the lateral membranes of T84 cells was significantly increased after treatment with either TNF-␣ or/and IFN-␥.…”
Section: The Expression Of Rage Is Up-regulated Under Inflammatory Comentioning
confidence: 99%